2015
DOI: 10.1093/femsle/fnv085
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of outer membrane vesicles from a neonatal meningitic strain of Cronobacter sakazakii

Abstract: Cronobacter sakazakii is associated with severe and often fatal cases of infant meningitis and necrotizing enterocolitis. The form of meningitis differs from that due to Neisseria meningitidis and Streptococcus spp., in that it is highly invasive and destructive towards human brain cells. However, there is relatively little understanding of the cytopathogenic interaction of C. sakazakii with host cells which results in stimulation of an inflammatory immune response. The production of Cronobacter outer membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 35 publications
3
20
1
1
Order By: Relevance
“…Bacterial OMPs play a crucial role in interaction of pathogens with host cells (Toma et al, 2014; Alzahrani et al, 2015; Bulir et al, 2015). OprF is the major OMP/porin of P. aeruginosa that has been demonstrated to facilitate biofilm formation under anaerobic conditions and adhesion to host cells (Azghani et al, 2002; Yoon et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial OMPs play a crucial role in interaction of pathogens with host cells (Toma et al, 2014; Alzahrani et al, 2015; Bulir et al, 2015). OprF is the major OMP/porin of P. aeruginosa that has been demonstrated to facilitate biofilm formation under anaerobic conditions and adhesion to host cells (Azghani et al, 2002; Yoon et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…We cannot, however, fully exclude the presence of cytoplasmic contaminants in the samples, which could contribute to a higher number of proteins been identified as cytoplasmic. The presence of several cytoplasmic proteins have, nonetheless, been identified in proteomic studies of several bacterial derived MVs [ 5 , 9 , 76 – 77 ], and it has been suggested that some of these proteins could be sorted into the vesicles during the MV formation [ 2 , 78 – 79 ]. This may implicate that the MV production is specific and not a random event, allowing for selective incorporation of proteins into the vesicles.…”
Section: Resultsmentioning
confidence: 99%
“…Together they represent several aspects of the bacteria, but in a non-replicative form. MVs have also been reported to contain several important immunogenic factors, such as toxins [ 8 ], chaperons [ 9 ], and active enzymes [ 5 ]. The mechanisms of the MV formation and their biological role have yet to be clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between OMVs and epithelial cells can modulate cellular mechanisms that control proliferation (Li et al, ), apoptosis (Kunsmann et al, ; Mondal et al, ), and ultimately immune responses. Cronobacter sakazakii , a causative agent of infant meningitis and enterocolitis, produces OMVs that are internalized by intestinal epithelial cells inducing cell proliferation, IL‐8 secretion and facilitating bacterial persistence (Alzahrani, Winter, Boocock, De Girolamo, & Forsythe, ).…”
Section: Immune Regulation and Pathogenesis Mediated By Omvsmentioning
confidence: 99%